Low-residue carbon lubricant for neodymium-iron-boron magnets and method of use

CN122879009APending Publication Date: 2026-10-09EARTH PANDA ADVANCE MAGNETIC MATERIAL +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611016804.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-09
Publication Date
2026-10-09

AI Technical Summary

Technical Problem

[0005]本发明的目的在于提供一种钕铁硼磁体用低残碳润滑剂及其使用方法,旨在解决目前钕铁硼专用润滑剂磁粉包覆不均匀、碳残留量高、磁粉流动差,进而影响磁体磁性能的技术问题,实现磁粉均匀包覆、超低残碳量、提高磁粉流动性进而提高钕铁硼磁体的磁性能

Benefits of technology

(1)强化学吸附与均匀包裹提升磁粉流动性:硼酸异辛酯与1,3-丙二醇富含羟基及高活性位点的硼酸酯极性基团。钕铁硼磁粉表面的活性金属位点对这些极性基团具有极强的化学亲和力。通过强化学吸附作用润滑剂分子可在磁粉表面自发形成一层致密、均匀的包覆层,解决了传统润滑剂因物理混合导致的局部团聚、包覆不均匀的问题,磁粉流动性提高30%以上。使用该润滑剂及制备工艺所制备的钕铁硼磁粉剩磁提高1%以上。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The application discloses a low-residual-carbon lubricant for a neodymium-iron-boron magnet and a use method thereof, and relates to the technical field of neodymium-iron-boron permanent magnet material preparation. The lubricant comprises isooctyl borate and 1,3-propylene glycol in a mass ratio of 75:25-90:10. The use method comprises the following steps: preparing an alloy rapid-cooling piece, crushing the alloy rapid-cooling piece to obtain magnetic powder; adding the lubricant into the magnetic powder and mixing the lubricant and the magnetic powder to realize surface coating; performing magnetic field orientation and compression molding on the mixed magnetic powder; then performing step-by-step degreasing and sintering in a vacuum sintering furnace, first keeping the temperature at 200-300 DEG C for 1-3 hours, then keeping the temperature at 300-400 DEG C for 1-3 hours, then increasing the temperature to 1000-1080 DEG C for sintering, and finally performing tempering heat treatment to obtain the magnet. Through the synergistic cooperation of the specific binary lubricant and the step-by-step degreasing process, the flowability of the magnetic powder is significantly improved, and an extremely low residual carbon content is realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of neodymium iron boron permanent magnet material preparation technology, and in particular to a low-carbon residual lubricant for neodymium iron boron magnets and its application method. Background Technology

[0002] Sintered NdFeB permanent magnets are widely used in new energy vehicles, wind power generation, energy-saving home appliances, and intelligent manufacturing due to their excellent magnetic properties. In the traditional production process of sintered NdFeB, the particle size of the magnetic powder after air jet milling is typically between 2 and 5 μm. This large surface area and high surface energy make the powder prone to agglomeration, resulting in poor powder flowability. This severely hinders the magnetic powder particles from rotating and aligning with the external magnetic field during the subsequent magnetic field orientation pressing process, thereby reducing the remanence of the magnet.

[0003] To address this issue, lubricants are typically added to the magnetic powder before or after air jet milling. Traditional lubricants often include zinc stearate, stearamide, oleic acid, or long-chain oligomers. While these traditional lubricants can reduce friction between powder particles to some extent, their long molecular chains (usually containing more than 16 carbon atoms) make them difficult to completely volatilize and decompose during the vacuum degreasing stage before sintering, leaving a large amount of carbon residue inside the magnet. This residual carbon reacts with the NdFeB main phase to form carbides, hindering grain boundary wetting, deteriorating the magnetic properties of the main phase, and leading to a significant decrease in magnetic performance.

[0004] Therefore, developing a special lubricant for NdFeB that can both effectively adsorb and uniformly coat NdFeB magnetic powder to improve its fluidity, and completely decompose at a lower temperature without leaving carbon residue, is a technical challenge that still needs to be solved in the preparation of high-performance sintered NdFeB magnets. Summary of the Invention

[0005] The purpose of this invention is to provide a low-carbon residual lubricant for NdFeB magnets and its application method, aiming to solve the technical problems of uneven magnetic powder coating, high carbon residue, and poor magnetic powder flow in current NdFeB-specific lubricants, which affect the magnetic properties of the magnets. The invention achieves uniform magnetic powder coating, ultra-low residual carbon content, and improved magnetic powder flowability, thereby improving the magnetic properties of NdFeB magnets.

[0006] The specific technical solution to achieve the above-mentioned objectives is as follows: In a first aspect, the present invention provides a low-carbon residual lubricant for neodymium iron boron magnets, comprising component A and component B, wherein the mass ratio of component A to component B is 75:25 to 90:10; Component A is isooctyl borate; component B is 1,3-propanediol.

[0007] Furthermore, the lubricant is thermally decomposed or volatilized within a temperature range of 200℃ to 400℃, and the residual carbon content after complete decomposition is <500ppm.

[0008] Furthermore, the mass ratio of component A to component B is 80:20 to 90:10.

[0009] Secondly, the present invention provides a method for preparing sintered NdFeB magnets using the above-mentioned lubricant, comprising the following steps: (1) Batching and smelting to prepare neodymium iron boron alloy quick-setting sheets; (2) The rapid-condensing sheet is subjected to hydrogen crushing and air jet milling to obtain neodymium iron boron magnetic powder; (3) Add the lubricant to the neodymium iron boron magnetic powder and mix it in a mixer so that the lubricant is evenly coated on the surface of the neodymium iron boron magnetic powder particles to obtain mixed magnetic powder; (4) The mixed magnetic powder is placed in a magnetic field molding machine for orientation pressing to obtain a pressed blank; (5) The pressed blank is placed in a vacuum sintering furnace and subjected to a stepwise degreasing and sintering process. The specific operation is as follows: first, the temperature is raised to 200℃~300℃ and held for 1h~3h, then the temperature is raised to 300℃~400℃ and held for 1h~3h; then the temperature is raised to 1000℃~1080℃ for sintering and held, and then tempering heat treatment is performed to obtain the neodymium iron boron magnet.

[0010] Furthermore, the D50 of the neodymium iron boron magnetic powder in step (2) is 2~5μm.

[0011] Further, the amount of lubricant added in step (3) is 0.05% to 0.3% of the total mass of the NdFeB magnetic powder.

[0012] Furthermore, the mixing time in step (3) is 2h to 10h.

[0013] Furthermore, the conditions for orientation pressing in step (4) include: the orientation magnetic field strength is 1.5-2.0T.

[0014] Furthermore, the sintering and holding temperature in step (5) is 1000℃-1080℃, and the holding time is 3-8h.

[0015] Furthermore, the tempering heat treatment in step (5) is a two-stage tempering treatment, specifically: the first-stage tempering temperature is 750℃-950℃, and the holding time is 1-5h; the second-stage tempering temperature is 400-600℃, and the holding time is 1-5h.

[0016] Furthermore, the Kelvin index of the NdFeB magnetic powder is <31%, and the carbon content of the prepared NdFeB magnet is <500ppm.

[0017] Compared with the prior art, the present invention has the following beneficial effects: (1) Strong chemical adsorption and uniform coating improve magnetic powder flowability: Isooctyl borate and 1,3-propanediol are boronic acid ester polar groups rich in hydroxyl groups and highly active sites. The active metal sites on the surface of NdFeB magnetic powder have a strong chemical affinity for these polar groups. Through strong chemical adsorption, lubricant molecules can spontaneously form a dense and uniform coating layer on the surface of magnetic powder, solving the problem of local agglomeration and uneven coating caused by physical mixing of traditional lubricants, and improving the flowability of magnetic powder by more than 30%. The remanence of NdFeB magnetic powder prepared using this lubricant and preparation process is increased by more than 1%.

[0018] (2) Low-temperature stepwise decomposition and ultra-low carbon residue: The binary lubricant system used in this invention is a short-chain compound, and its molecules contain easily cleaved ester bonds. In the relatively low temperature range of 200℃ to 400℃, the 1,3-propanediol with a smaller molecular weight is first removed by heating or vaporization at 200℃ to 300℃. Subsequently, in the temperature range of 300℃ to 400℃, isooctyl borate undergoes chain cleavage, and its hydrocarbon chains are completely converted into gaseous products that are removed by the vacuum system. Ultimately, an extremely low level of total residual carbon content of less than 500ppm can be obtained. Detailed Implementation

[0019] The technical solutions of this disclosure will be clearly and completely described below with reference to specific embodiments. However, those skilled in the art will understand that the embodiments described below are only some embodiments of this disclosure, not all embodiments, and are only used to illustrate this disclosure, and should not be regarded as limiting the scope of this disclosure. Based on the embodiments in this disclosure, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of this disclosure. Where specific conditions are not specified in the embodiments, conventional conditions or conditions recommended by the manufacturer shall be followed. Where the manufacturers of reagents or instruments are not specified, they are all conventional products that can be purchased commercially.

[0020] All raw materials used in the embodiments of this invention are commercially available industrial products. Specifically, isooctyl borate was purchased from Bied Pharmaceutical (CAS No.: 67989-25-7) with a purity of 98%; 1,3-propanediol was purchased from Tianjin Zhonglian Chemical Reagent (CAS No.: 504-63-2) with a purity of 99.5%. The invention will be described in detail below with reference to specific embodiments.

[0021] Example 1 This embodiment provides a specific method for preparing sintered NdFeB magnets using the lubricant of the present invention, which specifically includes the following steps: (1) After the NdFeB alloy is prepared by mixing the ingredients, it is placed in a vacuum melting furnace for melting and then prepared as NdFeB alloy quick-solidification sheet by quick-solidification process; (2) The rapid solidification sheet is subjected to hydrogen crushing and air jet milling to obtain neodymium iron boron magnetic powder with an average particle size (D50) of 3.52 μm; (3) A binary lubricant system was prepared by mixing isooctyl borate and 1,3-propanediol at a mass ratio of 85:15. The prepared binary lubricant system was thoroughly stirred and mixed to obtain a clear, uniform and transparent liquid. (4) Add the uniformly mixed lubricant to the NdFeB magnetic powder. The amount added is 0.2% of the mass of the NdFeB magnetic powder. Mix the powder in a 3D mixer at 500 rpm for 6 hours until the lubricant and NdFeB magnetic powder are evenly mixed. The discharged magnetic powder has a uniform and loose color, without sticking to the wall or oily agglomerates. The lubricant is evenly coated on the surface of the NdFeB magnetic powder particles. (5) The mixed neodymium iron boron magnetic powder is oriented and formed in a magnetic field molding machine. The orientation pressing is carried out under an orientation magnetic field of 2.0T, the forming pressure is 6MPa, and the holding time is 10s to obtain the pressed blank. During the pressing process, the NdFeB magnetic powder with good fluidity has less friction between particles during magnetic field orientation, thus improving the magnet orientation degree. (6) The pressed billet is put into the furnace for sintering and the temperature is raised in stages: the temperature is held at 240℃ for 1 hour, at 350℃ for 2 hours, and the sintering temperature is 1050℃ for 5 hours. Then, a second-stage tempering treatment is carried out: the first-stage tempering temperature is 860℃ and the temperature is held for 3 hours; the second-stage tempering temperature is 460℃ and the temperature is held for 3 hours.

[0022] Example 2 The difference between Example 2 and Example 1 is that the lubricant is a binary system lubricant composed of isooctyl borate and 1,3-propanediol in a mass ratio of 75:25.

[0023] Example 3 The difference between Example 3 and Example 1 is that the lubricant is a binary system lubricant composed of isooctyl borate and 1,3-propanediol in a mass ratio of 80:20.

[0024] Example 4 The difference between Example 4 and Example 1 is that the lubricant is a binary system lubricant composed of isooctyl borate and 1,3-propanediol in a mass ratio of 90:10. All other components are the same as in Example 1.

[0025] Example 5 The difference between Example 5 and Example 1 is that the mass of the lubricant is 0.1% of the mass of the neodymium iron boron magnetic powder, while all other aspects are the same as in Example 1.

[0026] Example 6 The difference between Example 6 and Example 1 is that the mass of the lubricant is 0.15% of the mass of the neodymium iron boron magnetic powder, while all other aspects are the same as in Example 1.

[0027] Example 7: The difference between Example 7 and Example 1 is that the mass of the lubricant is 0.25% of the mass of the neodymium iron boron magnetic powder, while all other aspects are the same as in Example 1.

[0028] Example 8: The difference between Example 8 and Example 1 is that the mass of the lubricant is 0.3% of the mass of the neodymium iron boron magnetic powder, while all other aspects are the same as in Example 1.

[0029] Example 9: The difference between Example 9 and Example 1 is that during the staged heating: the temperature was maintained at 300℃ for 1 hour and at 380℃ for 2 hours, while everything else was the same as in Example 1.

[0030] Comparative Example 1 This comparative example uses zinc stearate, a traditional lubricant, to prepare sintered NdFeB magnets, specifically including the following steps: (1) Prepare neodymium iron boron alloy quick-setting sheets by mixing and melting according to the formula; (2) The quick-setting sheet is subjected to hydrogen crushing and air jet milling to obtain neodymium iron boron magnetic powder, wherein the average particle size (D50) of the neodymium iron boron magnetic powder is 3.52 μm; (3) Using traditional lubricant zinc stearate, the amount added is 0.2% of the mass of NdFeB magnetic powder. Mix the powder in a 3D mixer at 500 rpm for 6 hours until the lubricant and NdFeB magnetic powder are evenly mixed and the lubricant is evenly coated on the surface of the NdFeB magnetic powder particles. (4) The mixed neodymium iron boron magnetic powder is placed in a magnetic field molding machine for orientation pressing and molding. The orientation pressing and molding is carried out under an orientation magnetic field of 2.0T, the molding pressure is 6MPa, and the holding time is 10s to obtain the pressed blank. (5) The pressed blank is sintered in a furnace at a temperature of 1050℃ for 5 hours, and then tempered. The tempering heat treatment is as follows: first-stage tempering: 860℃ for 3 hours; second-stage tempering: 460℃ for 3 hours, to obtain sintered NdFeB magnets.

[0031] Comparative Example 2 The difference between Comparative Example 2 and Comparative Example 1 is that DMF is used as the lubricant for neodymium iron boron magnetic powder, while everything else is the same as Comparative Example 1.

[0032] Comparative Example 3 The difference between Comparative Example 3 and Comparative Example 1 is that polyamide wax is used as the lubricant for neodymium iron boron magnetic powder, while everything else is the same as Comparative Example 1.

[0033] Comparative Example 4 The difference between Comparative Example 4 and Example 1 is that the lubricant is a binary system lubricant composed of isooctyl borate and 1,3-propanediol in a mass ratio of 70:30. All other parameters are the same as those in Example 1.

[0034] Comparative Example 5 The difference between Comparative Example 5 and Example 1 is that the lubricant is a binary system lubricant composed of isooctyl borate and 1,3-propanediol in a mass ratio of 99:1. All other parameters are the same as those in Example 1.

[0035] Comparative Example 6 The difference between Comparative Example 6 and Example 1 is that the phased heating parameters in step (6) are different: the temperature is kept at 150℃ for 1 hour and at 300℃ for 2 hours, while the other parameters are the same as those in Example 1.

[0036] Comparative Example 7 Compared with Example 1, Comparative Example 7 kept the lubricant ratio, addition amount and degreasing temperature unchanged, shortened the mixing time of step (4) to 1 hour, and kept the other process parameters the same.

[0037] Comparative Example 8 Compared with Example 1, Comparative Example 8 adjusted the step-by-step degreasing and heat preservation time in step (6), keeping the temperature at 240℃ for 0.5h and at 350℃ for 1h, while keeping the other process parameters the same.

[0038] Comparative Example 9 Compared with Example 1, Comparative Example 9 eliminated the stepwise degreasing process and directly heated the temperature to 1050°C for sintering, while the other process parameters remained the same.

[0039] The neodymium iron boron magnets prepared in the above embodiments and comparative examples were subjected to the following performance tests: (1) Remanence B r Tests were conducted according to the national standard GB / T 3217-2013 "Magnetic Test Methods for Permanent Magnet (Hard Magnetic) Materials"; (2) Karl index: The loose density and tapped density were measured according to the national standard GB / T 31057 "Test of Physical Properties of Particulate Materials"; Karl index (%) = (tapped density - loose density) / tapped density × 100%; (3) Carbon content: According to XB / T 617.6-2014 "Chemical Analysis Methods for Neodymium Iron Boron Alloys Part 6: Determination of Carbon Content by High Frequency-Infrared Absorption Method".

[0040] The test results are shown in Table 1.

[0041] Table 1

[0042] As shown in Table 1, Examples 1-9 represent the preferred embodiments of the present invention. A smaller Karl Fischer index indicates better powder flowability. The Karl Fischer indices of Examples 1-9 of the present invention range from 22.35% to 30.98%, all below 31%, while the Karl Fischer indices of Comparative Examples 1-7 with traditional lubricants are all above 45% (45.11%-49.87%), indicating that the magnetic powder flowability of the present invention is significantly superior to that of the prior art. Based on Comparative Example 1, the Karl Fischer index decreased by 37.9%-55.2% after adopting the scheme of the present invention (a decrease of 55.2% based on Example 1), resulting in a significant improvement in magnetic powder flowability. When the lubricant ratio exceeds the range of 75:25-90:10, the degreasing temperature is too low, or the stepwise degreasing process is omitted, the powder flowability deteriorates significantly. The best results are achieved when the mass ratio of isooctyl borate to 1,3-propanediol is controlled at 75:25 to 90:10, and the sintering process adopts a segmented degreasing process: holding at 200℃ to 300℃ for 1 to 3 hours and holding at 300℃ to 400℃ for 1 to 3 hours.

[0043] The remanence Br of the present invention embodiment is 13.14~13.25 kGs, which is about 1.6%~3.8% higher than that of Comparative Example 1 (12.75 kGs), and the magnetic properties are significantly improved.

[0044] The total carbon content of the finished products in all embodiments of the present invention is less than 500 ppm (minimum 395 ppm, maximum 461 ppm), which is far lower than that of the comparative example (minimum 687 ppm, maximum 1076 ppm), effectively avoiding the degradation of magnetic properties by carbon impurities.

[0045] The results confirm that the short-chain, multi-hydroxyl compound lubricant used in this invention can form strong chemical adsorption with the surface of NdFeB magnetic powder through its polar groups, resulting in a uniform coating on the magnetic powder surface and avoiding the defects of purely physical adsorption in traditional lubricants. Simultaneously, the non-polar short carbon chains of the molecules effectively reduce the frictional resistance between magnetic powder particles. Combined with a segmented degreasing process, the lubricant can be fully decomposed and removed, significantly reducing the residual carbon content in the magnet, ultimately achieving a simultaneous improvement in both the flowability of the magnetic powder and the magnetic properties of the magnet.

[0046] The embodiments described above are merely illustrative of several implementations of the present invention, and while the descriptions are relatively specific and detailed, they should not be construed as limiting the scope of the invention patent. It should be noted that those skilled in the art can make various modifications and improvements without departing from the concept of the present invention, and these all fall within the protection scope of the present invention. Therefore, the protection scope of this invention patent should be determined by the appended claims.

Claims

1. A low-carbon residual lubricant for neodymium iron boron magnets, characterized in that, It includes component A and component B, wherein the mass ratio of component A to component B is 75:25 to 90:10; Component A is isooctyl borate; component B is 1,3-propanediol.

2. The low-carbon residual lubricant for NdFeB magnets according to claim 1, characterized in that, The mass ratio of component A to component B is 80:20 to 90:

10.

3. A method for preparing sintered NdFeB magnets using the lubricant as described in claim 1, characterized in that, Includes the following steps: (1) Batching and smelting to prepare neodymium iron boron alloy quick-setting sheets; (2) The rapid-condensing sheet is subjected to hydrogen crushing and air jet milling to obtain neodymium iron boron magnetic powder; (3) Add the lubricant to the neodymium iron boron magnetic powder and mix it in a mixer so that the lubricant is evenly coated on the surface of the neodymium iron boron magnetic powder particles to obtain mixed magnetic powder; (4) The mixed magnetic powder is placed in a magnetic field molding machine for orientation pressing to obtain a pressed blank; (5) The pressed blank is placed in a vacuum sintering furnace and subjected to a stepwise degreasing and sintering process. The specific operation is as follows: first, the temperature is raised to 200℃~300℃ and held for 1h~3h, then the temperature is raised to 300℃~400℃ and held for 1h~3h; then the temperature is raised to 1000℃~1080℃ for sintering and held, and then tempering heat treatment is performed to obtain the neodymium iron boron magnet.

4. The method according to claim 3, characterized in that, The D50 of the neodymium iron boron magnetic powder mentioned in step (2) is 2~5μm.

5. The method according to claim 3, characterized in that, The amount of lubricant added in step (3) is 0.05% to 0.3% of the total mass of the neodymium iron boron magnetic powder.

6. The method according to claim 3, characterized in that, The mixing time in step (3) is 2h to 10h.

7. The method according to claim 3, characterized in that, The conditions for orientation pressing in step (4) include: the orientation magnetic field strength is 1.5-2.0T.

8. The method according to claim 3, characterized in that, The sintering and holding temperature in step (5) is 1000℃-1080℃, and the holding time is 3-8h.

9. The method according to claim 3, characterized in that, The tempering heat treatment mentioned in step (5) is a two-stage tempering treatment. The specific operation is as follows: the first-stage tempering temperature is 750℃-950℃, and the holding time is 1-5h; the second-stage tempering temperature is 400-600℃, and the holding time is 1-5h.

10. The method according to claim 3, characterized in that, The Kelvin index of the neodymium iron boron magnetic powder is <31%, and the carbon content of the prepared neodymium iron boron magnet is <500ppm.